The light of days the untold story of women resistance fighters in Hitler's ghettos - Batalion, Judith 1977- (Harper, an imprint of HarperCollinsPublishers, 2020)
Witnesses to the murder of their families and the destruction of their communities, a cadre of Jewish women in Poland became the nerves of a wide-ranging resistance network that fought the Nazis. The Light of Days reveials the real history of these women whose little-known feats have been eclipsed by time
Keywords: Geschichte 1939-1945; Jüdin; Nationalsozialismus; Widerstand; Polen; World War, 1939-1945 / Jewish resistance / Poland / Juvenile literature; Jewish women in the Holocaust / Juvenile literature; Holocaust, Jewish (1939-1945) / Poland / Personal narratives / Juvenile literature; Jews / Persecutions / Poland / Juvenile literature; World War, 1939-1945 / Poland / Juvenile literature; World War, 1939-1945 / Jewish resistance / Poland; Jewish women in the Holocaust; Holocaust, Jewish (1939-1945) / Poland / Personal narratives; Jews / Persecutions / Poland; World War, 1939-1945 / Poland; Jews / Persecutions; Poland; 1939-1945; Juvenile works; Personal narratives; Jugendbuch; Biografie